Effect of lanthanide ions stress on lactic acid fermentation performance of Streptococcus thermophilus during milk processing - Vargas Vargas, Maynor Alberto (2023)
The purpose of this research is to evaluate the inhibitory effect produced by the presence of lanthanide ions (Ln3+) at different concentrations on the biochemical process of lactic acid fermentation. Assays were carried out in reconstituted skim milk media with different contents of solids non-fat (SNF) by inoculation with Streptococcus thermophilus from commercially available freeze-dried, single-strain starter culture in Costa Rica, currently used in the manufacture of commercial cheese, yogurt, and other dairy products. Lanthanide elements find their main applications as structural components of electronic devices widely used in modern information and communication technologies (ICTs), among which cell phones, flat-screen televisions, hearing aids, desk computers, laptops, household appliances, and energy-saving fluorescent bulbs can be mentioned. In addition, they also play an important role in the manufacture of electric cars and wind turbines contributing to the development of alternative clean energies. Nevertheless, little progress has been made in developing recycling processes for the corresponding electronic waste containing these elements, which are being currently recognized as potential emerging pollutants in the environment. In this study, it was found significative inhibitory effects on the lactic acidification rate in the presence of lanthanides concentrations as low as 10-4 mol/L, at different incubation temperatures, incubation periods, and solid non-fat contents (SNF %), which might affect the quality and safety of some agro-industrial products of importance for the economy of the country, as well as some common biological processes such as the natural decomposition of organic matter and silage.